New steroidal glycosides from the fibrous roots of Ophiopogon japonicus. Issue 8 (3rd August 2018) - Duan, Chang-Ling; Li, Yu-Juan; Wang, Feng-Yun; Miao, Lan; Tang, Xu-Dong
Abstract: Two new steroidal glycosides (named fibrophiopogonins A, B), along with one known glycoside, were isolated from the fibrous roots of Ophiopogon japonicus (Liliaceae). Comprehensive spectroscopic analysis, including 2D NMR spectroscopy, and the results of acid hydrolysis allowed the chemical structure of the compounds to be assigned as 26-[( O - β -D-glucopyranosyl-(1 → 6)-D-glucopyranosyl)]-barogenin- 3- O -[ α -L-rhamnopyranosyl-(1→2)]- β -D-glucopyranoside and (25 R )-26-[( O - β -D-glucopyranosyl-(1→6)- β -D-glucopyranosyl)]- 3 β, 22α, 26- trihydroxyfurost- 5-ene-3- O -[ α -L-rhamnopyranosyl-(1→2)]- β -D-glucopyranoside. This is the first isolation of a cholestane glycoside with disaccharide moiety from a Ophiopogon species. The cytotoxic activities of1 ~3 against A375 and MCF-7 cells are described.